Is innovation in ICT valuable for the efficiency of Italian museums?. Issue 9 (2nd September 2022) - Guccio, Calogero; Martorana, Marco Ferdinando; Mazza, Isidoro; Pignataro, Giacomo; Rizzo, Ilde
ABSTRACT: This paper investigates the influence of information and communication technologies (ICT) on the efficiency in attracting visitors of Italian museums. Notwithstanding the extensive literature on museum performance measurement, the analysis of the role of technological innovation is relatively neglected. As a first attempt to fill this lacuna, this study presents a two-stage analysis of a novel sample of Italian state-owned museums built by merging information drawn from different sources. In the first stage, we use bootstrapped Data Envelopment Analysis (DEA) to measure the efficiency of museums. In the second stage, we use a bootstrap truncated regression approach to test the extent to which different forms of ICT affect museum efficiency. We distinguish the ICT investments into 'in situ' and online services, since the former improve the visitors' experience on site, while the latter can prepare for the visit or, even, be a substitute of the visit. The results reveal that the use of ICT is generally associated with better performances but 'in situ' services show to play a major role.